Tanggung Jawab Pelaku Usaha Snack Kiloan Memberikan Informasi Kepada Konsumen - Philip Savio Je (Comprehensive Law Journal, 2024)
Responsibility of Kiloan Snack Business Operators Giving Rights to Consumers. The two problems that are addressed and discussed in this script are: 1) Why are kilo snack business operators obliged to fulfill the right to consumer tray information?, 2) How to fulfill the responsibility of kilo snack business operators to fulfill the right to consumer tray information?The writing of the script uses a normative juridical method with primary and secondary legal materials. Primary legal materials are laws and secondary legal materials are journals, books, relevant dictionaries. Analysis of these basic legal materials uses legislation analysis and conceptual analysis. The results of this study show that for business people who produce kilo snacks are obligated to provide information through the inclusion of product labels on kiloan snack packages. The provision of this information is a basic consumer right to the one where this consumer right is protected by UUPK number 8 years 1999.